The four historical stages of urban ecology in Costa Rica (UNED Research Journal, 2018)
Urban ecology began in Costa Rica in the 1950s with the study of urban parasites, followed in the 1960s by the ecology of urban trees and in the 1990s by city ornithology. In 2008, with the creation of the first center in the world dedicated to the ecology of tropical settlements, the Urban Ecology Laboratory at UNED, the discipline began an institutional stage. The pioneers of the field in Costa Rica include Róger Bolaños, Luis Fournier, Gary Stiles and Zaidett Barrientos
Keywords: history of science in Costa Rica; research in cities; tropical urban biodiversity.